Kewenangan Pemerintah Daerah Dalam Pengharmonisasian, Pembulatan, Dan Pemantapan Konsep Raperda Provinsi Pasca Lahirnya UU No. 15 Tahun 2019 Tentang Perubahan Atas UU No. 12 Tahun 2011 Tentang Pembentukan Peraturan Perundang-Undangan - Oki Nugroho, Muhammad; Burlian, Paisol; Huzaimah, Arne (Jurnal Komunikasi Hukum, 2021)
This study analyzes the authority of the local government in harmonizing, unifying, and strengthening the concept of the Provincial Regional Regulation Draft. 15 of 2019 concerning Amendments to Law no. 12 of 2011 and their application in South Sumatra Province. The results of the analysis and discussion show that the regional government is not authorized to harmonize, unify, and consolidate the draft Provincial Regulation Draft after the issuance of Law No. 15 of 2019. After the issuance of this Law, harmonization, unification, and strengthening of the draft Provincial Regulation Draft are carried out by ministries or institutions that run a government in the field of law previously coordinated by the legal bureau (regional government apparatus). This activity is a form of deliberation in establishing law and one of the principles in Islamic nomocracy and democracy in Islam. The implementation of harmonization, unification, and consolidation of the draft Provincial Regulations in South Sumatra has not been under the provisions in Law No. 15 of 2019. The process of harmonizing, unifying, and strengthening the concept of the Draft Provincial Regulation in South Sumatra is still being implemented by the regional government (legal bureau as regional apparatus). Suggestions from researchers, namely that the provisions in Law no. 15 of 2019 and it is necessary to guide to human resources in the South Sumatra Province. This process needs to be linked to the concept ofÂ Maqhasid Syariah so that the substance of the Provincial Regulation does not conflict with the public interest (benefit).